1996
DOI: 10.1111/j.1432-1033.1996.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the DNA‐Binding Domain of the Tomato Heat‐Stress Transcription Factor HSF24

Abstract: Two-dimensional-NMR and three-dimensional-NMR experiments were performed to determine the solution structure of the DNA-binding domain of the tomato heat-stress transcription factor HSF24. Samples of uniformly "N-labeled and 15N,'3C-labeled recombinant proteins were used in the investigation. A near-complete assignment of the backbone 'H, '?N, and "C resonances was obtained by three-dimensional triple-resonance experiments, whereas three-dimensional '5N-TOCSY-heteronuclear-single-quantum-correlation-spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…The DBD domain contained three α-helix bundles and a small four-stranded antiparallel β-sheet as previously described in LpHsf24 (Fig.1) (Schultheiss et al, 1996). There was a conserved intron located near the 3′-end of the third helix ( Fig.1) Further analyses of the HR-A/B domain revealed that there were, in the majority of cases, three or more repeated heptads in the HR-A domain and two incompletely repeated heptads in the HR-B domain (Fig.2).…”
Section: Protein Structure and Classification Of Oshsfsmentioning
confidence: 99%
“…The DBD domain contained three α-helix bundles and a small four-stranded antiparallel β-sheet as previously described in LpHsf24 (Fig.1) (Schultheiss et al, 1996). There was a conserved intron located near the 3′-end of the third helix ( Fig.1) Further analyses of the HR-A/B domain revealed that there were, in the majority of cases, three or more repeated heptads in the HR-A domain and two incompletely repeated heptads in the HR-B domain (Fig.2).…”
Section: Protein Structure and Classification Of Oshsfsmentioning
confidence: 99%
“…Although the t-DBD of S-HsfA2 lacks strands b3 and b4, it contains the H2-T-H3 motif that is responsible for HSE recognition and binding based on analysis of the DBD structure of tomato (Solanum lycopersicum) HSF24 (Schultheiss et al, 1996). Thus, we hypothesized that S-HsfA2 might bind to the HSEs.…”
Section: S-hsfa2 Acts As An Hsfmentioning
confidence: 99%
“…2) in the winged helix-turn-helix DNA binding domain (Harrison et al 1994;Vuister et al 1994;Schultheiss et al 1996), an adjacent 80 residue hydrophobic repeat (HR-A/B) essential for trimer formation (Sorger and Nelson 1989;Clos et al 1990;Peteranderl and Nelson 1992), and the carboxy-terminal transactivation domain (Chen et al 1993;Green et al 1995;Shi et al 1995;Zuo et al 1995;Wisniewski et al 1996). With the exception of the HSF in budding yeast and human HSF4, another hydrophobic repeat (HR-C) is located adjacent to the transactivation domain; this repeat has been suggested to suppress trimer formation by interacting with HR-A/B (Nakai and Morimoto 1993;Rabindran et al 1993).…”
mentioning
confidence: 99%